Evaluation of Active Cooling Systems for Non-Residential Buildings - Mydin, M.A. Othuman (Individual Entrepreneur Kockkeshev Yu. K, 2014)
Cooling systems are an essential element in many facets of modern society including cars, computers and buildings. Cooling systems are usually divided into two types: passive and active. Passive cooling transfers heat without using any additional energy while active cooling is a type of heat transfer that uses powered devices such as fans or pumps. This paper will focus on one particular type of passive cooling: air-conditioning systems. An air-conditioning system is defined as controlled air movement, temperature, humidity and cleanliness of a building area. Air conditioning consists of cooling and heating. Therefore, the air-conditioning system should be able to add and remove heat from the area. An air-conditioning system is defined as a control or treatment of air in a confined space. The process that occurs is the air-conditioning system absorbs heat and dust while, at the same time, cleaning the air breathed into a closed space. The purpose of air-conditioning is to maintain a comfortable atmosphere for human life and to meet user requirements. In this paper, air-conditioning systems for non-residential buildings will be presented and discussed.